UPAYA MERUBAH PARADIGMA DALAM RANGKA MENINGKATKAN PENDAPATAN MASYARAKAT BERBASIS KOMUNITAS - Siti Suryani, Rambu Yetti Kalaway, Vindya Donna Adindarena (JURNAL TRANSFORMATIF UNKRISWINA SUMBA, 2018)
Poverty is identified with laziness and lack of community entrepreneurship, even though this perspective is not entirely true. In fact the statement "The Sumba People Are Lazy" denied by the people themselves. But why conditions have not really changed, even though assistance through poverty alleviation programs continues. The spirit of social entrepreneurship actually arises from some people who are actually ordinary people, they only have dreams that the people around him live better lives. Poverty must bethrown away, and the people must throw it away themselves. The church is one of theinstitutions in the community, which every week interacts with the congregation. Basedon the background above, the problem of this research is that the paradigm / mindset ofthe community addresses the life and livelihood that they have lived so far. There aretwo focus issues; 1) How to change the paradigm/mindset of the community? 2) Howmuch increase in people's income after experiencing a paradigm / mindset change? Thisstudy aims to find out 1) paradigm/mindset changes that occur in the community, and 2)Increased income of the people of Kamalapia village. Analysis tools are lineardevelopment analysis and free trend analysis. This study concludes that, 1) There hasbeen a development of paradigm/mindset changes in Kamalapia society for somepeople, that work will change their lives, and giving starts becomes a new habit forthem, namely through tithing and activity participation, so that there is a paradigm shifttowards abundant mentality, 2) There is an increase in family income that occursduring 6 months of assistance in stages up to 500 percent, from Rp. 300,000, to Rp.1,500,000.